2016
DOI: 10.1124/dmd.115.068601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling to Predict Midazolam Metabolite Exposure from In Vitro Data

Abstract: Methods to predict the pharmacokinetics of drugs in humans from in vitro data have been established, but corresponding methods to predict exposure to circulating metabolites are unproven. The objective of this study was to use in vitro methods combined with static and dynamic physiologically based pharmacokinetic (PBPK) models to predict metabolite exposures, using midazolam and its major metabolites as a test system. Intrinsic clearances (CLint) of formation of individual metabolites were determined using hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…In the present study, desipramine, an active metabolite of the tricyclic antidepressant imipramine, was selected as a test case to apply the approach of integrating in vitro data into static and dynamic PBPK models for metabolite exposure prediction following administration of parent drug, which was proposed in the previous study (Nguyen et al, 2016). Both imipramine and desipramine were demonstrated to undergo hydroxylation catalyzed by CYP2D6 (Brøsen and Gram, 1988;Sallee and Pollock, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, desipramine, an active metabolite of the tricyclic antidepressant imipramine, was selected as a test case to apply the approach of integrating in vitro data into static and dynamic PBPK models for metabolite exposure prediction following administration of parent drug, which was proposed in the previous study (Nguyen et al, 2016). Both imipramine and desipramine were demonstrated to undergo hydroxylation catalyzed by CYP2D6 (Brøsen and Gram, 1988;Sallee and Pollock, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…M18 can be formed from M2 or M20; however, for modeling purposes it was assumed that it is formed solely from M2 (supported by the observation that M2 is the major route of metabolism). Hence, the systemic clearance of the secondary metabolite M18 (CL M18 ) was calculated according to equation CnormalLM18=normalfm,218×CnormalLM2×AUnormalC0M2AUnormalC0M18where f m,2‐18 is the fraction of M2 forming M18, CL M2 was the systemic clearance of M2 calculated from equation , AUC 0‐∞M2 was the observed area under the plasma concentration‐time curve of M2 (from rifampin interaction study), and AUC 0‐∞M18 was the observed area under the plasma concentration‐time curve of M18 (from the human mass balance study).…”
Section: Methodsmentioning
confidence: 99%
“…The authors acknowledged that some pharmacologic or toxicologic endpoints might be C max driven, and that predictions of metabolite C max would require additional in vivo data on the metabolite. Recently, Nguyen et al (2016) described a mechanistic approach for predicting the pharmacokinetics of midazolam and its metabolites using in vitro data and a physiologically based pharmacokinetic model. The predicted AUC ratios of metabolite (1-OH and 4-OH midazolam) to parent drug were in good agreement with clinical observations, and the model also afforded predicted plasma concentration versus time curves of midazolam and its metabolites.…”
Section: Discussionmentioning
confidence: 99%